MANAJEMEN KRISIS PUBLIC RELATIONS PT. MITRA AGUNG SWADAYA DALAM MEMBENTUK CITRA POSITIF PADA PT. MAS KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Safitri, Rani; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Crisis management is one of the tasks of public relations practitioners when the company is in a state of crisis, crisis management is formed by public reations to solve the problems that cause the crisis occurs in one organization. The emergence of news related to waste disposal by the company negatively impacted the image of the company that was initially well received by the external public, This study aims to know how the crisis management stages and crisis management strategies undertaken by PT.Mitra Agung Swadaya to handle the image crisis that happened. The research uses qualitative research methods that try to explain the phenomenon that occurs in accordance with the results obtained by using 7 subjects as an informant research using purposive technique. The data collected by collecting the information obtained through observation, interview and documentation, the researcher uses anailsis data technique using interactive data model with validity checking data done with triangulation technique and reference adequacy. The data obtained are then processed to be reduced and analyzed, presented until a general conclusion is produced. The results of this study indicate that crisis management used by public relations is done quickly. Public relations formed crisis management after realizing that the state of the company is not good, begun by collecting data in the field. making crisis management stages further divided into pre-crisis stages by forming crisis management teams of 5 people delivering crisis messages and establishing channels of communication through the media, providing crisis responses to maintain data accuracy, determining spokespersons to sympathize with residents affected by waste disposal and post crisis by monitoring the state of crisis. Establish a crisis management strategy that begins by determining a potential firm's crisis, identifying the affected audiences, and creating contingency plans to create a pool of waste that is endorsed by the community.